A real-world study on the clinicopathological profile, treatment outcomes and health-related quality of life, anxiety and depression among patients with desmoid tumor at two tertiary care centers in India - Tansir, Ghazal; Sharma, Aparna; Biswas, Bivas; Sah, Suryadev Narayan; Roy, Somnath; Deo, S. V. S.; Agarwala, Sandeep; Khan, Shah Alam; Bakhshi, Sameer; Pushpam, Deepam (Frontiers in Oncology, 2024)
BackgroundThe medical management of DT comprises tyrosine kinase inhibitors (TKIs), hormonal agents, anti-inflammatory drugs with the recently approved gamma secretase inhibitor nirogacestat being the current standard of care. Real-world data on evolving treatment landscapes of DT remains scarce.MethodsThis is a retrospective study of patients with DT registered between 1995 and 2020 at All India Institute of Medical Sciences, New Delhi and Tata Medical Center, Kolkata. Baseline characteristics were analyzed in form of median values and interquartile range. Categorical and continuous variables were compared by chi square and independent samples T- tests respectively. Anxiety, depression and QoL were prospectively measured among 30 patients using Hospital Anxiety and Depression (HADS) and Functional Assessment of Cancer Therapy-General (FACT-G) scales respectively between 2022 to 2023.Results200 patients were included with a male-predominant (n=111, 55.5%) population and median age 26.5 (2.5-75) years. Extremity (n=100, 50%) and abdomen (n=65, 32.5%) were commonest primary sites and median of 2 (1–4) lines of treatment were received. First-line included surgery (n=116, 58%), systemic therapy (n=67, 33.5%), radiotherapy (10, n=5%) and active surveillance (n=7, 3.5%). First-line systemic agents included tamoxifen (n=55, 27.5%), imatinib (n=7, 3.5%), sorafenib (n=1, 0.5%) and chemotherapy (n=4, 2%). 2019 onward, 3% and 63% underwent active surveillance and surgery respectively. Best radiological response obtained with tamoxifen was stable disease (SD) (n=76, 59%) and partial response (PR) (n=31, 24.2%). Best radiological response obtained with sorafenib was PR (n=17, 60.7%) and SD (n=9, 32.1%). Thirty patients underwent HADS and FACT-G scale assessment. Mean HADS-Anxiety subscale score was 3.6 (+/-3.9 SD) and HADS-Depression sub-scale score was 2.6 (+/-3.5 SD) with clinically significant anxiety and depression in 2 (6.7%) patients each. The overall mean FACT-G score was 87.5 (+/-12.6 SD) and lower mean physical well-being (p=0.006) and emotional well-being (0.017) scores were significantly associated with higher HADS-anxiety (>/=8) scores.ConclusionsAssessment of anxiety, depression and QoL are paramount to gauge the psychological impact of DT. This study gives an overview of clinical and management profile of patients with DT in India, with limitations of selection bias, heterogeneous population and small sample size for QoL assessment.